Ophthalmic anterior segment metastasis masquerading as uveitis. Issue 3 (2nd March 2021) - Nguyen, Quang Le; Reynolds, Samuel Benjamin; Piri, Niloofar; Rivas Perez, Hiram L
Abstract : Ocular malignancies are rare, with many cancers of the eye being the result of metastases, the most common of which result from primary tumours of breast, lung and gastrointestinal tract. Diagnosis is often made at a late stage in the disease course, leading to poorer outcomes. Disease-directed therapy in the presence of ocular metastases varies based on the primary tumour and patient performance status but generally involves systemic treatment, either with chemotherapy or involved-field radiation. We herein present an interesting case of ocular malignancy with neuroendocrine small cell features of pulmonary origin in a patient with no prior oncological history. Meticulous ophthalmic examination led to the diagnosis of small cell lung carcinoma with anterior segment metastasis. The patient underwent six cycles of systemic chemotherapy with a favourable response, resulting in improvement in vision and regression of the ocular lesion.